Preparation method and application of pH-responsive drug carrier polymer with transmembrane transitivity

The synthesis of pH-responsive drug carrier polymers with transmembrane transferability through the triblock polymer method has solved the pH response and transmembrane transfer problems of nanodrug carriers in the infected microenvironment in the prior art, and achieved efficient targeting Drug release and significant antibacterial effects.

CN119463195APending Publication Date: 2025-02-18DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411571507.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

There is a lack of research on the structure-activity relationship between the morphological changes and responsiveness of polymer segments, enrichment targeted drug release rate, and antibacterial and anti-inflammatory effects of existing nanodrug carriers before and after pH response in the infected microenvironment and before and after transmembrane transmission.

Method used

The three-block polymer method was used to synthesize pH-responsive drug carrier polymers with transmembrane transferability, and the tri-embedded PAE segment, PEG-b-PAE two-segment prepolymer and PEG-b-PAE-g-TAT Segment transmembrane delivers pH-responsive polymers.

Benefits of technology

The active transmission of nanodrugs in the vascular barrier is achieved, the enrichment targeted drug release rate is improved, the critical micelle concentration is reduced, the micelle morphology is ensured in the blood circulation system, and the high biosafety is demonstrated and Significant antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463195A_ABST
    Figure CN119463195A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a pH response drug carrier polymer with transmembrane transitivity. The preparation method specifically comprises the following steps: step 1, synthesizing a PAE chain segment; step 2, synthesizing a PEG-b-PAE two-chain segment precursor by adopting the product obtained in the step 1; and step 3, synthesizing a PEG-b-PAE-g-TAT three-block transmembrane delivery pH response polymer by adopting the product obtained in the step 2, namely the pH response drug carrier polymer with transmembrane delivery property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the research of nano drug delivery, and in particular to a preparation method and application of a pH-responsive drug carrier polymer with transmembrane transferability. Background Art

[0002] Nano drug delivery systems (DDS) can be divided into four categories: inorganic nanomaterials, metal-organic framework (MOF) nanomaterials, polymer nanomaterials and non-covalently assembled nanomaterials, including liposomes, micelles, hydrogels, microspheres, dendrimers, inorganic nanoparticles, organic-inorganic hybrid nanoparticles and protein carriers. However, among these numerous carrier materials, nano polymer micelles have attracted more and more attention and research from researchers in the past two decades due to their advantages such as easy structural design, easy synthesis and modification, low immunogenicity and low preparation cost. With the continuous breakthroughs in the research results of nano drug delivery systems in the treatment of bacterial infections, it can achieve highly targeted and controlled release, improve patient compliance with drugs, and has become an important direction for the development of modern targeted sustained-release pharmaceutical materials. Stimuli-responsive targeted drug delivery systems can use internal or external stimuli such as temperature, specific enzymes, redox, light and magnetic fields to improve the targeting of nano drugs. pH is the most representative and most commonly used internal stimulus in pathological sites, such as tumors and inflammatory tissues, as well as physiological environments such as acidic organelles. Therefore, we developed drug carriers with active transmembrane delivery function based on pH responsiveness.

[0003] After being captured by cells through different endocytic pathways (macropinocytosis, caveolin or cell membrane caveolae), nanomedicines will enter the intracellular sorting network. Generally, drugs distributed to the Golgi apparatus can achieve transcytosis, while drugs transported to lysosomes are easily degraded and lose their effect. After entering the Golgi apparatus, nanomedicines that are internalized by cells can be expelled from cells through exocytosis, achieving transcellular transmission and penetration based on active transcytosis mechanisms. In the process of targeted drug delivery, if nanomedicines want to remain in the blood circulation system for a long time and effectively penetrate in inflammatory tissues, they need to have surface properties that do not adhere to cells and proteins to obtain "concealment"; however, once they reach the vicinity of inflammatory tissue cells, nanomedicines need to "de-conceal" to restore their ability to bind to cells so that they can be adsorbed onto tumor / inflammatory tissue cells faster and trigger adsorption-mediated transcytosis. The intermolecular interaction between PEG and phospholipids is very weak, and it has the characteristics of electrical neutrality and strong hydrophilicity, and almost no intermolecular adhesion with proteins, so it can avoid being adsorbed by plasma proteins or cleared by the reticuloendothelial system, thus having a longer blood circulation time. The above research results have laid the foundation for the preparation of active transmembrane delivery drug delivery systems based on PEG or zwitterionic polymer segments. These systems have demonstrated the possibility of active transmembrane delivery and revealed the active transcytosis process, but there is still a lack of research on the structure-activity relationship between polymer micelles before and after pH response in the infection microenvironment and before and after transmembrane delivery, changes in the molecular structure of polymer segments and responsiveness, enrichment of targeted drug release rate, and antibacterial and anti-inflammatory effects. Summary of the invention

[0004] The main purpose of the present invention is to provide a preparation method and application of a pH-responsive drug carrier polymer with transmembrane transportability, so as to solve the above-mentioned technical problems.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is: a method for preparing a pH-responsive drug carrier polymer with transmembrane transportability, which specifically comprises the following steps:

[0006] Step 1, synthesizing PAE segments;

[0007] Step 2, using the product obtained in step 1 to synthesize a PEG-b-PAE two-segment precursor;

[0008] Step 3, using the product obtained in step 2 to synthesize a PEG-b-PAE-g-TAT triblock transmembrane delivery pH responsive polymer, that is, a pH responsive drug carrier polymer with transmembrane delivery;

[0009] The step 1 specifically includes the following steps:

[0010] Step 11, adding monomer 1,6-hexanediol diacrylate into a reaction container filled with chloroform and stirring;

[0011] Step 12, immerse the reaction bottle in liquid nitrogen to freeze, evacuate, then take it out of the liquid nitrogen and thaw it with room temperature water;

[0012] Step 13, after repeatedly performing step 12 three times, ventilate the reaction bottle with nitrogen and seal it for a period of time;

[0013] Step 14, after performing step 12, returning the reaction container and the solution therein to room temperature;

[0014] Step 15, adding 3-amino-1-propanol to the reaction vessel at a certain speed using a constant pressure dropping funnel under a certain stirring speed;

[0015] Step 16, after the dropwise addition is completed, react for a period of time at room temperature under nitrogen protection;

[0016] Step 17, transferring the solution obtained in step 15 to an oil bath at a certain temperature to continue reacting for a period of time;

[0017] Step 18: After the reaction is completed, cool to room temperature and freeze-dry to obtain a light yellow colloidal product PAE.

[0018] Preferably, the step 2 specifically includes the following steps:

[0019] Step 21, dissolving the PAE and polyethylene glycol diamine obtained in step 1 in chloroform according to a certain mass ratio and reacting for a period of time;

[0020] Step 22, removing chloroform from the product of step 21 by rotary evaporation;

[0021] Step 23, transferring the product obtained in step 22 to a dialysis bag and dialyzing it with deionized water for a period of time to remove unreacted monomers;

[0022] Step 24, collecting the solution in the dialysis bag, centrifuging and freeze-drying the solution to obtain a PEG-b-PAE two-segment precursor.

[0023] Preferably, in step 23, the dialysis time is 48 hours, the deionized water is replaced every 2 hours in the first 12 hours, the deionized water is replaced every 4 hours in the middle 12 hours, and the deionized water is replaced every 6 hours in the last 24 hours;

[0024] Preferably, the step three specifically includes the following steps:

[0025] Step 31, maleimide polyethylene glycol and Cys-TAT are placed in a solvent of dimethyl sulfoxide (DMSO) at a mass ratio of 4:1, and triethylamine is added as a catalyst, and stirred at a certain speed for a period of time to obtain NH2-PEG2000-TAT;

[0026] Step 32: NH 2 -PEG 2000 -TAT is added to the product obtained in the second step, and the mixture is reacted for a period of time at room temperature under nitrogen protection;

[0027] Step 33, after the reaction in step 32 is completed, wash with dichloromethane, and repeatedly wash with cold n-hexane several times;

[0028] Step 34, placing the product obtained in step 33 into a pretreated dialysis bag with a molecular weight cutoff of 5k Da, sealing the bag and performing dialysis for a period of time;

[0029] Step 35: After dialysis, freeze-drying is performed to obtain a pure white solid product PEG-b-PAE-g-TAT, which is a pH-responsive drug carrier polymer with transmembrane transportability.

[0030] Preferably, in step 34, the dialysis time is 48 hours, the deionized water is replaced every 2 hours in the first 8 hours, the deionized water is replaced every 4 hours in the middle 16 hours, and the deionized water is replaced every 6 hours in the last 24 hours.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] Higher enrichment targeting: The present invention introduces cell-penetrating peptides with transmembrane transmission properties by designing the structure of the three-block polymer carrier, thereby realizing the active delivery of the nano-drug system across the vascular barrier, and improving the enrichment targeting drug release rate compared to traditional passive targeting. This has been well verified in the in vitro antibacterial experiment of Staphylococcus aureus, with a minimum inhibitory concentration MIC of 6.25μg / mL and a minimum bactericidal concentration MBC of 0.03mg / mL. In the plate coating test, the sample was configured to a working concentration of 50μg / mL and acted on a diluted bacterial solution of 106CFU / ml. The antibacterial rate against Staphylococcus aureus was 99.90%. At the minimum dilution multiple (10 times), the number of colonies was 6, and there was almost no colony growth, indicating that the antibacterial effect of the sample was very obvious. In addition, the cell uptake experiment of cancer cells also demonstrated its better cell delivery effect.

[0033] Lower critical micelle concentration: The critical micelle concentration of the nanopolymer carrier synthesized by the triblock polymerization method in PBS buffer solutions with pH values ​​of 5.0, 6.0 and 7.4 is 4.6 mg / L, 5.8 mg / L and 10.4 mg / L respectively. The lower critical micelle concentration ensures its micelle morphology in the blood circulation system, which is about 30% lower than that of other block polymers of the same type at pH = 7.4.

[0034] Higher biosafety: The pH-sensitive block in the triblock polymer is a cationic polymer (PAE) of the poly(β-amino ester) type, which has simple synthesis, easy structural modification and good biodegradability. Compared with other types of pH-sensitive blocks such as polyethyleneimine (PEI), it has very high biosafety. In addition, the presence of the polyethylene glycol (PEG) block also ensures its low irritation when circulating in the body. This has been verified in cytotoxicity experiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is the chemical reaction formula of the present invention;

[0036] Figure 2 It is the mechanism diagram of drug delivery system;

[0037] Figure 3 It is the FT-IR spectra of monomer, prepolymer and target polymer;

[0038] Figure 4 It is prepolymer PAE, NH 2 -PEG-TAT and target polymer PEG-b-PAE-g-TAT 1 H-NMR spectrum;

[0039] Figure 5 is the pH-V titration curve of the target polymer PEG-b-PAE-g-TAT;

[0040] Figure 6 It is the curve (25℃) of I338 / I333 value in PBS buffer solution with different pH values ​​(pH=7.4, 6.0 and 5.0) versus the concentration of polymer solution;

[0041] Figure 7 The particle size distribution of drug-loaded micelles at different pH values ​​when the polymer-loaded CIP and TPCA-1 have an optimal ratio of polymer: CIP: TPCA-1 of 4:2:1;

[0042] Figure 8 is the drug release curve of polymer-loaded CIP drug-loaded micelles in PBS at different pH;

[0043] Fig. 9 is the survival rate of MEFs / M330 cells after treatment with different concentrations of polymer micelles for 24 hours;

[0044] Fig.10 is the MIC result of the drug delivery system against Staphylococcus aureus;

[0045] Fig.11 is the MBC result of the drug delivery system against Staphylococcus aureus;

[0046] Fig.12 are inverted fluorescence microscopy images of A549 cells co-cultured with free DOX, DOX-PMs, and DOX / TPCA-1 for 0.5 h;

[0047] Fig.13 are inverted fluorescence microscopy images of A549 cells co-cultured with free DOX, DOX-PMs, and DOX / TPCA-1 for 2 h;

[0048] Fig.14 Inverted fluorescence microscopy images of A549 cells co-cultured with free DOX, DOX-PMs, and DOX / TPCA-1 for 4 h. DETAILED DESCRIPTION

[0049] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.

[0050] Example

[0051] A method for preparing a pH-responsive drug carrier polymer with transmembrane transportability comprises the following steps:

[0052] Step 1: Synthesizing the PAE segment, specifically comprising the following steps:

[0053] Step 11, adding the monomer 1,6-hexanediol diacrylate (HDODA) into an eggplant-shaped reaction bottle and placing a stirring bar, the eggplant-shaped reaction bottle is pre-placed with a solvent chloroform, and the stirring bar starts stirring;

[0054] Step 12, immerse the reaction bottle in liquid nitrogen to freeze, evacuate, then take it out of the liquid nitrogen and thaw it with room temperature water;

[0055] Step 13, after repeating step 12 three times, nitrogen is introduced into the reaction bottle and sealed for a period of time;

[0056] Step 14, after executing step 13, returning the reaction bottle and the solution therein to room temperature;

[0057] Step 15, adding 3-amino-1-propanol (AP) to the reaction bottle at a rate of 10 s / drop using a constant pressure dropping funnel under a stirring speed of 120 r / min, the mass ratio of HDODA to AP being 1.1:1;

[0058] Step 16: After the dropwise addition is completed, react at room temperature under nitrogen protection for 2 hours;

[0059] Step 17, transfer the solution obtained in step 15 to a 100°C oil bath and continue the reaction for 5 hours;

[0060] Step 18: After the reaction is completed, cool to room temperature and freeze-dry to obtain a light yellow colloidal product PAE.

[0061] Step 2: Synthesizing the PEG-b-PAE two-segment precursor, specifically comprising the following steps:

[0062] Step 21, PAE obtained in step 1 and polyethylene glycol diamine (NH 2 -PEG-NH 2 ) was dissolved in chloroform at a ratio of 1.1:1 and reacted at room temperature for 24 hours;

[0063] Step 22, removing the solvent chloroform from the product of step 21 by rotary evaporation;

[0064] Step 23, transferring the product obtained in step 22 to a dialysis bag (molecular weight cutoff [MWCO] 3500)) and dialyzing with deionized water for 48 hours to remove unreacted monomers; specifically, the deionized water was replaced every 2 hours for the first 12 hours, the deionized water was replaced every 4 hours for the middle 12 hours, and the deionized water was replaced every 6 hours for the last 24 hours;

[0065] Step 24, collecting the solution in the dialysis bag, centrifuging and freeze-drying the solution to obtain a PEG-b-PAE two-segment precursor.

[0066] Step 3: Synthesizing PEG-b-PAE-g-TAT triblock transmembrane pH-responsive polymer, specifically comprising the following steps:

[0067] Step 31, maleimide polyethylene glycol NH2-PEG2000-Mal and Cys-TAT are placed in a solvent of dimethyl sulfoxide DMSO at a mass ratio of 4:1, and triethylamine is added as a catalyst, and the mixture is reacted at a stirring speed of 120 r / min for 24 hours to obtain NH2-PEG2000-TAT;

[0068] Step 32: NH 2 -PEG 2000 -TAT was added to the diblock polymer product of the second step, and the reaction was carried out under nitrogen protection and at room temperature for 24 hours;

[0069] Step 33, after the reaction in step 32 is completed, wash the transferred product with dichloromethane into a beaker, and wash it repeatedly with cold n-hexane three times;

[0070] Step 34, the product obtained in step 33 is placed in a pretreated dialysis bag with a molecular weight cutoff of 5k Da, and the bag is sealed for dialysis for 48 hours. Specifically, the deionized water is replaced every 2 hours for the first 8 hours, the deionized water is replaced every 4 hours for the middle 16 hours, and the deionized water is replaced every 6 hours for the last 24 hours.

[0071] Step 35: After dialysis, freeze-drying is performed to obtain a pure white solid product PEG-b-PAE-g-TAT, which is a pH-responsive drug carrier polymer with transmembrane transportability.

[0072] Test Case

[0073] (1) Polymer structure characterization

[0074] The polymer structure was analyzed by FT-IR and 1H-NMR. The functional groups of the synthesized polymer were analyzed by Spectrum Two Fourier infrared spectrometer from PERKIN ELMER, USA. The infrared spectrum was obtained and the corresponding data was saved by PerkinElmer Spectrum IR software. The scanning number was 20 times, and the measurement range was 400-4000cm-1. The carbon-hydrogen structure of the synthesized polymer was analyzed by nuclear magnetic resonance hydrogen spectrum (1H-NMR). An appropriate amount of polymer was dissolved in deuterated DMSO (C 2 D 6 SO), 25°C, and detected by Bruker AVANCE III 400 (250 MHz, Switzerland). The obtained spectral data were analyzed by Mestre Nova software.

[0075] from Figure 3 It can be seen that in the infrared spectrum of PAE, 2933 cm -1 The absorption peak is =CH stretching vibration, 1727cm -1 The absorption peak at 1200cm is a strong absorption peak representing the stretching vibration of the C=O bond of esters. -1 and 1056cm -1 There are two stretching vibration peaks of CO bond. -1 The absorption peak at 3400cm is the stretching vibration peak of the C=C double bond. TAT is a polypeptide structure containing a guanidine group, in addition to a terminal carboxyl group and a phenolic hydroxyl group. From its infrared spectrum, we can see that 3400cm -1 and 3150cm -1The hydroxyl stretching vibration peak of the carboxyl group and the typical double absorption peak of the primary amine group are at 1640 cm -1 800cm -1 The double peaks at 1125cm are the in-plane bending vibration absorption peak and the out-of-plane bending vibration absorption peak of the NH bond. -1 The infrared spectrum of Cys-TAT of thiol-modified TAT is not much different from that of TAT. The characteristic absorption peaks of -SH and -OH bonds are in similar positions, so it is difficult to distinguish them from the infrared spectrum. Nuclear magnetic resonance hydrogen spectrum can be used for further comparative analysis. Compared with the infrared spectrum of diamino polyethylene glycol, maleimide-modified amino polyethylene glycol has no absorption peaks in the three regions of NH bond stretching vibration, in-plane and out-of-plane bending vibration, because it is connected to tertiary amine and there is no hydrogen atom on the nitrogen atom. However, the peak at 1100cm -1 The stretching vibration absorption peak of the CN bond at 2885cm is much stronger. The infrared spectrum of the final synthesized target polymer basically retains the characteristic peaks of PAE, diamino polyethylene glycol and amino-modified TAT. -1 The peak at 1709cm -1 The absorption peak at 1460cm is the stretching vibration absorption peak of the NH bond and C=O bond in the peptide bond. -1 and 839cm -1 The absorption peaks at 1106 cm-1 are the in-plane and out-of-plane bending vibration peaks of NH. -1 The stretching vibration absorption peak of the CN bond is still very strong. From the above infrared results analysis, it can be seen that the triblock polymer has been basically synthesized.

[0076] In order to further confirm the structure of the compound, the intermediates and final products were 1 H-NMR characterization. Figure 4 As shown, Figure 4 The characteristic chemical shift of 7.31 in the top curve comes from the -OH hydrogen proton peak, 4.06 and 3.7 come from CH 2 =Three hydrogen proton peaks on CH-, 2.81 from -CH 2 The hydrogen proton peak in -COO-, 2.63 from and N-(CH 2 -) 3 The hydrogen proton peak in the 2 The hydrogen proton peaks in -O-, 1.63 and 1.39 come from the methylene group -CH 2 -The proton peak of hydrogen on the upper surface. From the above NMR results analysis, it can be seen that the PAE precursor has been synthesized. Figure 4 The middle curve is maleimide butyric acid modified polyethylene glycol diamine, that is, maleimide polyethylene glycol amine (NH2-PEG-Mal) reacts with thiol Cys-TAT to generate NH2 -PEG-TAT prepolymer H NMR spectrum. The hydrogen proton peak of the maleimide group NH at the chemical shift of 7.0ppm disappeared, indicating that the maleimide group was reacted. The hydrogen proton peak of the terminal primary amine at the chemical shift of 2.5ppm increased a lot because of the addition of the TAT group. The chemical shift at 3.4ppm is still -CH 2 -CH 2 -Hydrogen proton peak, chemical shift at 3.6ppm is -CH 2 The hydrogen proton peak in -O-. Figure 4 The bottom curve and NH 2 Compared with the NMR spectrum of -PEG-TAT, there are 4.06ppm and 3.7ppm more from CH 2 =Three hydrogen proton peaks on CH-, 2.7ppm comes from -CH 2 The hydrogen proton peak in -COO-, 2.43ppm comes from and N-(CH 2 ) 3 -, the hydrogen proton peak area of ​​the 2.5ppm terminal primary amine is reduced, and the 1.63ppm and 1.39ppm are from the methylene group -CH 2 -The proton peak of hydrogen on the upper surface. Compared with the PAE NMR spectrum, there is little change, except that the hydroxyl peak disappears significantly. From the above NMR results, it can be seen that PAE prepolymer, NH 2 -PEG 2000 -TAT prepolymer and polyethylene glycol diamine were polymerized to generate the target polymer.

[0077] Gel permeation chromatography (GPC) was used to analyze the size and distribution of the polymer molecular weight to further verify the correctness of the synthesis results. GPC was used to detect the number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the polymer. 5-10 mg of the polymer to be tested was prepared with THF to prepare 1 mg / mL and 5 mg / mL solutions for testing. The column was calibrated with monodisperse polystyrene standards, chromatographically pure THF was used as the mobile phase, the flow rate was 1.0 mL / min, and the temperature was 30°C.

[0078] Table 1 Molecular weight and distribution of polymers at different polymerization stages

[0079] In order to further verify the polymer structure, we tested the molecular weight of the polymer synthesized in each step. The test results are shown in Table 1. The number average molecular weight Mn of the prepolymer PAE is 3683, the weight average molecular weight Mw is 4383, the diacrylate-1,6-hexanediol ester is slightly excessive, and the prepolymer PAE is terminated with acrylate groups. Therefore, the polymerization degree X of PAE is estimated to be about 9, and the molecular weight distribution index PDI = Mw / Mn = 1.19. The prepolymer PAE is successfully synthesized. The two-block prepolymer PAE-NH 2 -PEG 4000 -NH 2 -PAE molecular weight test results show that the number average molecular weight is 6134, the weight average molecular weight is 10964, and the molecular weight distribution index PDI = Mw / Mn = 1.78, which is between 1.5 and 2.0, indicating that the molecular weight distribution of the polymer is relatively uniform. The number average molecular weight of the precursor PAE is 3683, and the weight average molecular weight of NH 2 -PEG 4000 -NH 2 The molecular weight of PAE-NH 2 -PEG 4000 -NH 2 The degree of polymerization of -PAE is about 1:1. Before the third step of polymerization, the prepolymer NH 2 -PEG 2000 -TAT, and then PAE-NH 2 -PEG 4000 -NH 2 The triblock polymer PEG-b-PAE-g-TAT was polymerized, and its number average molecular weight was 11983, the weight average molecular weight was 18068, and the molecular weight distribution index PDI = Mw / Mn = 1.51, indicating that the molecular weight distribution of the final polymer was also relatively uniform.

[0080] (2) Determination of polymer pH responsiveness and CMC value

[0081] Potentiometric titration was used to evaluate the pH sensitivity of polymers. Weigh 25 mg of the polymer to be tested and ultrasonically dissolve it in 5 ml of deionized water, then add 20 ml of deionized water and stir for 30 minutes until it is completely dissolved. Use homemade 0.01 mol / L dilute hydrochloric acid to adjust the pH of the solution, and use pH test paper to roughly determine that the pH value of the solution is 3 to prepare the pre-titration solution. The pre-titration solution is titrated with sodium hydroxide aqueous solution (0.1 mol / L) using an automatic potentiometric titrator and computer operation to record the pH value and titration end point in real time at room temperature. The pKa value is determined by calculating the relationship between the pH value and the volume of the sodium hydroxide solution.

[0082] The pKa value of the triblock polymer was determined by potentiometric titration to evaluate the pH responsiveness of the polymer. The pH-V titration curve was plotted with the volume of titrated NaOH as the abscissa and the pH value as the ordinate. Figure 5 It can be seen that when the pH value rises to the range of 5.5-6.8, a platform area appears in the polymer. The reason may be that the protonated part of the PAE in the polymer block is converted into the deprotonated part during the titration process, which inhibits the rise of the pH value. This shows that the pH response value is about 6.3. After that, as the amount of alkali solution added continues to increase, the pH value rises sharply again.

[0083] The critical micelle concentration (CMC) was determined by the fluorescent probe method. Hydrophobic pyrene was selected as the fluorescent probe and dissolved in acetone to prepare the solution. Weigh 0.6 mmol of pyrene and dissolve it in 100 mL of acetone to prepare a 6×10-3 mol / L pyrene solution. Then transfer 1 mL of the pyrene solution and add 100 mL of acetone to dilute the solution to 6×10-5 mol / L. Take 21 10 mL volumetric flasks, add 0.1 mL of 6×10-5 mol / L pyrene solution to each, and leave it for 24 hours to evaporate the acetone. Accurately weigh 10 mg of polymer and dissolve it in 5 mL of acetone. Then accurately add 100 mL of PBS buffer solution (pH=5, 6, 7.4) and stir for 24 hours to evaporate the acetone to obtain a 0.1 mg / mL polymer mother solution. On the second day, after the acetone had evaporated, an appropriate amount of polymer mother liquor was measured and used to prepare sample solutions with concentrations varying from 0.0001 mg / mL to 0.1 mg / mL with acetone.

[0084] Use a fluorescence spectrophotometer to determine the critical micelle concentration of the polymer. After setting the parameters and test methods using the FL Solution software, execute Measure to perform scanning measurements. Set the Excitation excitation spectrum mode, and use an excitation wavelength of 373nm to scan the wavelength range of 250-360nm, and select a slit width of 2.5nm. After the test is completed, save the data and images, take the ratio of I1 / I3=I338 / I333 or I337 / I335 and plot it against the logarithm of the concentration logC, fit the two curves, and calculate the intersection to get the CMC value.

[0085] The CMC values ​​of polymer micelles formed by polymer self-assembly were studied by fluorescence spectroscopy in PBS buffer solutions with pH values ​​of 7.4, 6.0, and 5.0 to determine the micelle formation process and the stability of the system. 338 / I 333 The ratio is plotted against the logarithm of the polymer concentration, as Figure 6As shown. As the pH value decreases from 7.4, 6.0 to 5.0, the CMC value of the polymer gradually increases from 4.6 to 5.8 and 10.4 mg / L. When the pH gradually decreases. The amine groups in the hydrophobic PAE segments are gradually ionized, causing the PAE segments to change from hydrophobic to hydrophilic. A greater driving force is required to offset the repulsive force generated by the longer hydrophilic segments, so a higher concentration is required to form a micelle structure. In a neutral environment, the CMC value of the polymer can reach 4.6 mg / L, which ensures the circulation of the drug delivery system in the body.

[0086] (3) Determination of drug-loaded micelle particle size, drug loading and encapsulation efficiency

[0087] The micelle size was measured by dynamic light scattering (DLS). 1 mg of the sample was dissolved in 10 ml of PBS buffer with different pH values, stirred with a stirrer for 30 minutes, then sonicated for 2 minutes, stopped for 1 minute, and repeated 5 times. The sample was then placed in a laser particle size analyzer for detection.

[0088] The particle size distribution of drug-loaded micelles formed by coating with polymers in a ratio of 5:2:1 in polymer:CIP:TPCA-1 in buffer solutions with different pH values. The specific values ​​of particle size and potential are shown in Table 7. It can be seen from the figure that the particle size gradually increases with the decrease of pH, especially when pH=5.0, the particle size increases to more than 450nm, indicating that the micelles become loose and the particle size continues to increase with the decrease of pH value. The particle size at pH=7.4 is about 200nm, which meets the range requirement of the nano drug delivery system with a particle size of less than 220nm.

[0089] The drug loading of ciprofloxacin in the drug-loaded micelles was determined by UV-visible spectrophotometry. Accurately weigh 1 mg of polymer drug-loaded micelles and dissolve them in 10 mL of deionized water. Stir for 45 minutes to fully dissolve them. Deionized water was used as the control solution, and the absorbance of the solution was checked at a characteristic wavelength of 282 nm using a UV spectrophotometer. The drug loading and encapsulation efficiency in the micelles were calculated using the following formula to check the drug loading.

[0090] Encapsulation efficiency EE (%) = mass of loaded drug / mass of delivered drug × "100%",

[0091] Drug loading LC (%) = mass of loaded drug / mass of drug-loaded micelles × "100%".

[0092] Table 2 Drug loading and encapsulation efficiency of CIP-loaded nanomicelles

[0093] As can be seen from Table 2, when the dosage is 5 mg, the polymer micelles can basically completely encapsulate CIP. The hydrophobic effect of CIP allows the drug to enter the blank micelles better. CIP can also form hydrogen bonds with the polymer molecular groups through its own carboxyl groups and enter the blank micelles as a load. These factors will increase the drug loading of the nano micelles. However, the dosage of 5 mg is too little. At this time, the lowest drug loading LC is only 8.37%, so it is not the best feed ratio. As the dosage increases, the drug loading LC gradually increases, up to 29.81%. However, the encapsulation rate at 10 mg, 15 mg, 25 mg, and 40 mg is not as high as that at 20 mg, so it is not the best feed ratio. In summary, the best feed ratio of the drug delivery system is 50 mg polymer mass and 20 mg drug mass, which can encapsulate the drug to the greatest extent, the encapsulation rate EE can reach 85.21%, and the drug loading LC is 25.42%.

[0094] (4) Determination of drug release from drug-loaded micelle system in vitro

[0095] The drug release capacity of drug-loaded micelles in buffer solutions with different pH values ​​was detected by ultraviolet spectrophotometer to simulate the release of drugs from micelles under different physiological conditions. pH = 7.4, 6, and 5 were selected to simulate the release of drugs under normal physiological conditions, in the microenvironment of bacterial infection, and in lysosomes. 5 mg of ciprofloxacin-loaded polymer micelles were weighed and dissolved in 5 mL of PBS buffer solution (pH = 7.4, 6, and 5). The three solutions were respectively loaded into dialysis bags with a molecular weight cutoff of 3.5 kDa and the bag mouth was sealed. The dialysis bag was placed in a release medium of 250 mL of PBS buffer solution (pH = 7.4, 6, and 5), and the release study was carried out at 37°C and 120 r / min under the constant speed condition of a heated magnetic stirrer. At the predetermined time points of 0.25, 0.5, 1, 2, 4, 7, 17, 23, 31, 40, and 48 hours, 4 ml of sample solution was taken out from the beaker, and 4 ml of fresh PBS solution was added after each sampling to keep the total volume of the sample constant. The dialysate collected at each time point was measured at 280 nm using a UV-visible spectrophotometer. The concentration of CIP was calculated based on the CIP standard working curve, and the cumulative drug release was calculated using the following formula, and a related curve was drawn.

[0096]

[0097] Where: Er is the cumulative release rate of CIP (%), Ve is the sampling volume (mL), V0 is the total volume of the release medium (mL), Ci is the concentration of the drug at the i-th sampling (mg / mL), Cn is the concentration of the drug at the n-th sampling (mg / mL), W is the total mass of the drug in the drug-loaded micelles (mg), and n is the number of samplings.

[0098] Figure 8 The simulated in vitro drug release behavior curve of 50mg polymer: 20mg CIP loaded micelles in PBS at 37℃ and different pH. As can be seen from the figure, when the pH is 7.4, the drug release rate is relatively slow overall, and the overall release rate is about 38% after 48h. As the pH value decreases, the drug release rate accelerates. In the first 7h, the CIP release amounts at various pH values ​​are 17.4%, 42.4% and 54.7% respectively; after 48h, the drug release amount under pH=5 is as high as 91.9%, which once again proves the pH responsiveness of the polymer. Therefore, the drug release test results of ciprofloxacin within 48h also reflect that the polymer loaded micelles have good sustained release function. When the pH is lowered, the overall release rate of the drug is higher, reflecting its good pH responsiveness.

[0099] (5) Cytotoxicity assay

[0100] The CCK-8 method was used to determine the cytotoxic effect of drug-loaded micelles. Preparation of pure polymer micelle solution: 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, and 500 mg / L polymer solutions were prepared, dissolved in DMEM / F12 complete culture medium, and stored in a 4°C refrigerator.

[0101] A549 cancer cells and MEFs / M033 cells in the logarithmic growth phase were taken for cell inoculation and culture. After the cells were attached to the 48-well plate for 24 hours, they were taken out and observed under an inverted microscope. After the cells were completely attached to the wall, they were sprayed with an alcohol spray bottle for disinfection, placed in a clean bench, and the culture medium in the well plate was extracted with a pipette gun, and the prepared polymer micelle solution was re-added. The well plate was then placed in a CO2 constant temperature cell culture incubator (37°C, 5% CO2) and cultured for 24 hours. 100 μL of the prepared CCK-8 solution was added to each well of the 48-well plate, and after adding, it was placed in a CO2 constant temperature cell culture incubator (37°C, 5% CO2) and cultured for 1 hour before being taken out. After that, the cell growth was detected using an enzyme marker. The solution in the 48 wells was transferred to a 96-well plate, and after adding the CCK-8 solution for 1 hour, the absorbance of each well in the 96-well plate was measured using an enzyme marker, and the absorbance of the well was measured at 450nm, and the absorbance results were recorded.

[0102] Table 3 Survival rate of A549 cells after treatment with different gradient concentrations of polymers for 24h, 48h and 72h

[0103] The toxicity of the polymer to human non-small cell lung cancer A549 cells was determined by the CCK-8 method to explore the biosafety of the polymer. As shown in Table 3, when the polymer concentration was 150 mg / L or less, the cell survival rate was greater than 90% after incubation for 48 hours and 72 hours, indicating that the polymer toxicity was negligible at this time. When the polymer concentration was greater than 150 mg / L, the cell survival rate decreased slightly with the increase of the polymer concentration, until the cell polymer concentration was greater than 250 mg / L, the cell survival rate dropped below 90%. Even if the polymer concentration reached a higher 400 mg / L and the action time was as long as 72 hours, 69.5% of the cells still survived, indicating that the polymer itself had little toxic effect on A549 cells.

[0104] like Fig. 9 As shown in the figure, after culturing with different concentrations of polymer micelles for 24 hours, the concentration gradually increased from 150 mg / L, but the cell survival rate was still maintained at a high level. Even when the polymer concentration reached 350 mg / L, the survival rate of the treated cells was still as high as over 90%. In summary, the micelles used for drug encapsulation are non-toxic to cancer cells and non-cancerous cells, and the polymers have good biocompatibility in tumor cells and normal cells in in vivo applications.

[0105] (6) Antibacterial test

[0106] The antibacterial effect of the drug delivery system on Staphylococcus aureus was evaluated by measuring the inhibition zone, plate coating, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) tests.

[0107] Fig.10 and Fig.11 The results showed that the minimum inhibitory concentration (MIC) of the CIP-loaded polymer micelle drug delivery system against Staphylococcus aureus was 6.25 μg / ml and the minimum bactericidal concentration (MBC) was 0.03 mg / ml at a dosage ratio of 50 mg:20 ml, indicating that it has a good bactericidal effect at lower concentrations.

[0108] Table 4 Plate coating count results of Staphylococcus aureus

[0109] Table 4 shows the plate count results of the control group and the drug-loaded system, that is, the antibacterial rate of the 50mg:20ml micelle sample against Staphylococcus aureus is 99.90% when the working concentration is 50mg / L. At the minimum dilution multiple (10 times), the colony count is 6, and there is almost no colony growth, indicating that the antibacterial effect of the sample is very obvious.

[0110] (7) Cell uptake experiment

[0111] The doxorubicin DOX used in this experiment has fluorescent properties and can be used as an anticancer drug to treat cancer cells. The excitation wavelength of doxorubicin is 480nm and the emission wavelength is 586nm. TPCA-1 (5-(4-fluorophenyl)-2-ureidothiophene-3-carboxamide) needs to produce fluorescence under different excitation lights, while DOX has its own red fluorescence. The experimental principle is to use DAPI reagent, which is a blue fluorescent dye that can specifically bind to DNA. It is often used to stain cell nuclei. By overlapping with the red fluorescence of DOX, a fluorescent microscope can be used to observe the distribution of drugs in cells, thereby characterizing the enrichment and targeting effect of the drug delivery system.

[0112] From the fluorescence images of free DOX drugs in each group, it can be seen that after 0.5 h of co-culture ( Fig.12 ), 2 hours( Fig.13 )、4 hours( Fig.14 ), a strong pink-purple fluorescence signal can be observed in the cell nuclei of each group, indicating that the release rate of free drug is very fast. It can be taken up by cancer cells in 0.5 hours and reacts rapidly in tumor cells. This also reflects that the free drug has high cytotoxicity. The release rate is too fast, which will cause excessive damage to the release site, indicating that the toxic side effects of unencapsulated free DOX are very strong.

[0113] By comparing the fluorescence images of each group of DOX-PMs and DOX / TPCA-1 micelles, it can be seen that after 0.5 hours of co-cultivation, the red fluorescence of DOX in the DOX-PMs micelle group was not strong, and the DOX / TPCA-1 micelle group almost had no red fluorescence. After 2 hours of co-cultivation, the red fluorescence in the nucleus of the two micelle groups was still not strong. After 4 hours of co-cultivation, the red fluorescence of the DOX / TPCA-1 micelle group in the nucleus and the area near the nucleus was enhanced, and the pink-purple fluorescence signal after fusion became stronger, indicating that the DOX / TPCA-1 micelles have a sustained release function. The amount of DOX absorbed by cells continues to increase over time, and finally the cell uptake effect is better than that of free DOX, indicating that it has good enrichment and targeted drug release.

[0114] Experimental example

[0115] This experimental example 1 is applicable to NH 2 -PEG-NH 2 Monomer triblock polymers: Select different molecular weight NH 2 -PEG-NH 2 According to PAE:NH 2 -PEG-NH 2 :NH 2 -PEG 2000-TAT=1:1:1 ratio to synthesize polymer. 1a is NH with molecular weight M.W1000 2 -PEG-NH 2 Monomer, 2a is NH with molecular weight M.W2000 2 -PEG-NH 2 Monomer, 3a is NH with molecular weight M.W4000 2 -PEG-NH 2 Monomer. Three drug-loaded polymers with different hydrophilic block lengths were prepared and their performances were compared. The polymerization method was based on the synthetic route of the PEG-b-PAE two-segment precursor.

[0116] This experimental example 2 is applicable to PAE, NH 2 -PEG-NH 2 NH 2 -PEG2000-TAT triblock polymers with different block ratios: 2a triblock polymer with a monomer ratio of PAE:NH 2 -PEG-NH 2 :NH 2 -PEG 2000 -TAT=1:1:1; 2b The monomer ratio of the triblock polymer is PAE:NH 2 -PEG-NH 2 :NH 2 -PEG 2000 -TAT=1:1:2; the monomer ratio of 2c triblock polymer is PAE:NH 2 -PEG-NH 2 :NH 2 -PEG 2000 -TAT=2:1:1. Polymerization method reference Figure 3 Synthesis route.

[0117] This experimental example 3 is applicable to drug-loaded systems with different dosing ratios: the polymer mass is 50 mg, and different amounts of ciprofloxacin CIP are added, namely 3a 5 mg, 3b 10 mg, 3c 15 mg, 3d 20 mg, and 3e 25 mg. The drug-loaded micelles were prepared by dialysis.

[0118] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a pH-responsive drug carrier polymer with transmembrane transportability, characterized in that: The specific steps include: Step 1, synthesizing PAE segments; Step 2, using the product obtained in step 1 to synthesize a PEG-b-PAE two-segment precursor; Step 3, using the product obtained in step 2 to synthesize a PEG-b-PAE-g-TAT triblock transmembrane delivery pH responsive polymer, that is, a pH responsive drug carrier polymer with transmembrane delivery; The step 1 specifically includes the following steps: Step 11, adding monomer 1,6-hexanediol diacrylate into a reaction container filled with chloroform and stirring; Step 12, immerse the reaction bottle in liquid nitrogen to freeze, evacuate, then take it out of the liquid nitrogen and thaw it with room temperature water; Step 13, after repeatedly performing step 12 three times, ventilate the reaction bottle with nitrogen and seal it for a period of time; Step 14, after performing step 12, returning the reaction container and the solution therein to room temperature; Step 15, adding 3-amino-1-propanol to the reaction vessel at a certain speed using a constant pressure dropping funnel under a certain stirring speed; Step 16, after the dropwise addition is completed, react for a period of time at room temperature under nitrogen protection; Step 17, transferring the solution obtained in step 15 to an oil bath at a certain temperature to continue reacting for a period of time; Step 18: After the reaction is completed, cool to room temperature and freeze-dry to obtain a light yellow colloidal product PAE.

2. The method for preparing a pH-responsive drug carrier polymer with transmembrane transportability according to claim 1, characterized in that: The step 2 specifically includes the following steps: Step 21, dissolving the PAE and polyethylene glycol diamine obtained in step 1 in chloroform according to a certain mass ratio and reacting for a period of time; Step 22, removing chloroform from the product of step 21 by rotary evaporation; Step 23, transferring the product obtained in step 22 to a dialysis bag and dialyzing it with deionized water for a period of time to remove unreacted monomers; Step 24, collecting the solution in the dialysis bag, centrifuging and freeze-drying the solution to obtain a PEG-b-PAE two-segment precursor.

3. The method for preparing a pH-responsive drug carrier polymer with transmembrane transportability according to claim 2, characterized in that: In step 23, the dialysis time is 48 hours. The deionized water is replaced every 2 hours in the first 12 hours, the deionized water is replaced every 4 hours in the middle 12 hours, and the deionized water is replaced every 6 hours in the last 24 hours.

4. The method for preparing a pH-responsive drug carrier polymer with transmembrane transportability according to claim 2, characterized in that: The step three specifically includes the following steps: Step 31, maleimide polyethylene glycol and Cys-TAT are placed in a solvent of dimethyl sulfoxide (DMSO) at a mass ratio of 4:1, and triethylamine is added as a catalyst, and stirred at a certain speed for a period of time to obtain NH2-PEG2000-TAT; Step 32, adding NH2-PEG2000-TAT to the product obtained in the second step, and reacting for a period of time under nitrogen protection and at room temperature; Step 33, after the reaction in step 32 is completed, wash with dichloromethane, and repeatedly wash with cold n-hexane several times; Step 34, placing the product obtained in step 33 into a pretreated dialysis bag with a molecular weight cutoff of 5k Da, sealing the bag and performing dialysis for a period of time; Step 35: After dialysis, freeze-drying is performed to obtain a pure white solid product PEG-b-PAE-g-TAT, which is a pH-responsive drug carrier polymer with transmembrane transportability.

5. The method for preparing a pH-responsive drug carrier polymer with transmembrane transportability according to claim 4, characterized in that: In step 34, the dialysis time is 48 hours. In the first 8 hours, the deionized water is replaced every 2 hours. In the middle 16 hours, the deionized water is replaced every 4 hours. In the last 24 hours, the deionized water is replaced every 6 hours.

6. Use of a pH-responsive drug carrier polymer with transmembrane transportability prepared according to the preparation method of any one of claims 1 to 5 in nanomedicine.